Self-regulated learning of nursing students: a cross-sectional study - Romli, Muhammad Hibatullah; Wan Yunus, Farahiyah; Hamzah, Siti Aishah; Abas, Razif; Chan, Choong Foong (Penerbit Universiti Sains Malaysia, 2022)
The nursing degree programme requires the students to be resilient due to the high learning burden of theoretical courses and clinical attachment requirements. The ability of the students to self-regulate their learning has been postulated for success. In this study, we aim to investigate the self-regulated learning level of nursing students at one public institution and identify the self-regulation aspects that warrant a remediation plan to be developed. A cross-sectional survey was conducted online. Active status students in one public institution’s Bachelor of Nursing programme were invited to participate in this study. The invitation was distributed online via social media and email, where they are required to self-administer the Motivated Strategies for Learning Questionnaire (MSLQ) through Google Forms. Thereafter, responses from 63 students with a response rate of 64.3% were received. Most respondents are female (76.2%), Malay (74.6%), in year 4 of their bachelor’s study (33.3%), and in the lower household income category (69.8%). Most self-regulation aspects of the students have been found to be at a satisfactory level except for specific learning strategies. Participants’ characteristics such as gender, ethnicity, study cohort, and academic achievement were determined to have a significant association with a small aspect of self-regulation. Interestingly, household income is the primary factor significantly associated with almost all self-regulation aspects. Being in the lower-income category was predominantly associated with higher motivation domains. In contrast, being in the middle-income category was predominantly associated with better learning strategies and resources. Comparatively, this study indicates that nursing students achieved the highest level in 8 of 15 self-regulation aspects than other learner populations in Malaysia. Learning strategies which exercise higher autonomy and resource management are warranted. This recommended various approaches which foster active and collaborative learning to be implemented for the students to improve their self-regulation skills. Students, especially from the highest income bracket, are the most critical and thus require attention from educators.